Compression test of c-section cold-formed steel with an opening - Muhammad Azammuddin, Mohd Norman (2019)
Single sections are the first choice before built-up sections used to resist load induced in a structure for example roof trusses. An existence of perforation in the structural member can be benefit to mechanical and electrical works, aside from that, theoretically the ultimate strength of the structure will be reduce due to existence of openings. This paper presents a detailed description of an experimental study of the flexural buckling strength in the presence of a perforation of cold-formed steel column. A total of 8 short columns, each length 600 mm, vary in size (203 mm and 103 mm) and thickness (1.3 mm and 2.0 mm). Compression test were done by using Universal Testing Machine and the ultimate strength were observed. The test result of 4 specimens with an opening were compared to the ones without opening. The result is presented in three section which are load vs vertical displacement, load vs horizontal displacement and buckling behaviour.